Consumers Favor "Right Brain" Training: The Dangerous Lure of Neuromarketing. Issue 1 (24th February 2013) - Lindell, Annukka K.; Kidd, Evan
ABSTRACT Over the past decade the neuromarketing of educational products has become increasingly common. Researchers have however expressed concern about the misapplication of neuroscience to education marketing, fearing that consumers may be deceived into investing in apparently "brain‐based" products under the misapprehension that they will be more effective. This study provides the first demonstration that these fears are justified. We presented 180 participants with one of four advertisements for an identical educational program, named either "Right Brain" or "Right Start" Training; the advertisements either did, or did not, include an MRI brain image in one corner. Results demonstrated that "Right Brain" training was deemed more interesting, educationally valuable, and scientifically strong than an identical product named "Right Start" training. Advertisements including an unrelated brain image enhanced ratings of scientific rationale. These results confirm that by implying a strong scientific basis, "brain‐based" product names are remarkably effective in implicitly manipulating consumer opinion.